BAHAN AJAR MENULIS OPINI DAN ESAI DENGAN PEMBELAJARAN BERBASIS PROYEK - Sakaria Sakaria; Asis Nojeng (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
Abstract: The Instructional Writing Material of Opinion and Essays with Problem Based Learning. This study aims to describe the feasibility and effectiveness of writing articles of opinion and project-based essay articles. Teaching materials were developed using the ADDIE model at the Muhammadiyah University of Makassar. The results showed that the developed teaching materials have been feasible and effectively used in the study of opinion writing and essay. The teaching materials are worthy of use because they meet the aspects of eligibility that are content feasibility, presentation feasibility, and language feasibility. Effective teaching materials are used because there are significant differences in student learning outcomes before using and after using teaching materials.